Rozwód w internetowym dyskursie prawniczym - Wismont, Magdalena (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2019)
The article’s focus is on the creation of the notion of divorce in online legal discourse. The study material comes from an Internet forum discussing legal issues. The analysis shows that divorce is generally presented as a conscious decision of an individual; one that requires preparation and often time and effort as well. Moreover, it is a crucial point in life at which the divorcees solve their current problems. The term is also associated with new opportunities and is often a chance to talk about human experience. The article distincts the most frequently-used words accompanying divorce: child, alimony, money and flat. It is worth noting that the studied material uses only one meaning of the word divorce, introduced by the Napoleonic Code and understood as ‚a dissolution of legally-valid marriage’.